The choice of approach in total hip arthroplasty, does it really matters? - Subramanian, Sukumaran Subbiah; Sengodan, Mugundhan Moongilpatti; Basha, Masoodh M. (International Journal of Research in Medical Sciences, 2017)
Background: Various surgical approaches have been described for total hip arthroplasty with their own advantages and disadvantages. In the study it would like to know whether there is significant difference exists between the most widely used posterior and lateral approaches. Methods: Study was a randomized prospective study in 108 hips. Out of 108 hips 52 were operated by posterior approach and the remaining 56 by lateral approach. The choice of approach was determined by random numbers. In the study functional outcome was compared with the Harris hip score, rate of complications and the effect of approach on the placement of acetabular cup with relation to its inclination and version in arthroplasty of the hip. Results: Similar results in both approaches were found; there were no statistically significant difference in the outcome. Conclusions: To conclude, the approach did not significantly affect the outcome in total hip replacement with respect to functional outcome or rates of complication. And it neither influences the acetabular cup placement. Proper operative technique seems to be more important than the choice of approach in total hip replacement. Studies with a bigger sample size need to be done to further throw light on the role of approach on cup placement.